The Ability of Compost Materials Containing Entomopathogen Metarhizium anisopliae (Metsch.) Sorokin to Suppress Oryctes rhinoceros L. Larvae - Fauzana, Hafiz; Kortima, Eka; nelvia, Nelvia; Rustam, Rusli; Puspita, Fifi (Badan Penerbitan Fakultas Pertanian (BPFP), Fakultas Pertanian, Universitas Bengkkulu, 2022)
Oryctes rhinoceros is one of the main pests in oil palm plantations. Biological control using Metharizium anisopliae has great potential to control O. rhinoceros larvae which are usually found in organic matter. This study aims to obtain the best organic compost material for the development of M. anisopliae as biological control against O. rhinoceros larvae. This research was conducted with a completely randomized design (CRD) consisting of 6 treatments, each treatment was repeated 5 times to obtain 30 experimental units. Each unit contained 10 O. rhino larvae. The concentration of M. anisopliae was 50 g / L of distilled water. The treatments of organic media consisted of 6 setting media, as follows: Oil Palm Empty Fruit bunch (OPEFB), rice husk, sawdust, ½ part OPEFB + ½ sawdust, ½ part OPEFB + ½ part rice husk, and ½ part rice husk + ½ part sawdust. The observations included the time of initial death, time of death, daily mortality, total mortality, changes in behavior and larvae morphology. Chemical analysis of OPEFB, temperature, and humidity were recorded. The results showed that compost from sawdust media had the tendency as the best media for the development of Metarizhium anisopliae. It had ability to infect O. rhinoceros larvae which caused larvae infection 72.50%.